2017
DOI: 10.1161/jaha.117.005586
|View full text |Cite
|
Sign up to set email alerts
|

Thymosin Beta‐4 Is Elevated in Women With Heart Failure With Preserved Ejection Fraction

Abstract: BackgroundThymosin beta‐4 (TB4) is an X‐linked gene product with cardioprotective properties. Little is known about plasma concentration of TB4 in heart failure (HF), and its relationship with other cardiovascular biomarkers. We sought to evaluate circulating TB4 in HF patients with preserved (HFpEF) or reduced (HFrEF) ejection fraction compared to non‐HF controls.Methods and Results TB4 was measured using a liquid chromatography and mass spectrometry assay in age‐ and sex‐matched HFpEF (n=219), HFrEF (n=219) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Nine of the 15 proteins with differential levels across phenogroups have previously been associated with HF and comorbidities in independent data sets using the same proximity eThese trials have relied only on signsxtension assay proteomics chip (online supplementary table S7), and an additional two proteins in previous work on partly the same patients with HFpEF as in this study,18 lending support to the importance of these proteins in HF disease processes. Of these FGF-23, PlGF, NEMO, sST2, TRAIL-R2, U-PAR have previously been associated with HF incidence and HFpEF,28 29 and all, except NEMO and sST2, have also been associated with CKD or kidney dysfunction 30. FGF-23 and U-PAR have also been associated with incident AF 31.…”
Section: Discussionmentioning
confidence: 98%
“…Nine of the 15 proteins with differential levels across phenogroups have previously been associated with HF and comorbidities in independent data sets using the same proximity eThese trials have relied only on signsxtension assay proteomics chip (online supplementary table S7), and an additional two proteins in previous work on partly the same patients with HFpEF as in this study,18 lending support to the importance of these proteins in HF disease processes. Of these FGF-23, PlGF, NEMO, sST2, TRAIL-R2, U-PAR have previously been associated with HF incidence and HFpEF,28 29 and all, except NEMO and sST2, have also been associated with CKD or kidney dysfunction 30. FGF-23 and U-PAR have also been associated with incident AF 31.…”
Section: Discussionmentioning
confidence: 98%
“…Drum et al have reported the detection of endogenous Ac‐Tβ4 in the plasma of healthy human volunteers, but the urine samples were not tested for detecting the endogenous Ac‐Tβ4 29 . On the contrary, by the study of Mora et al, the basal levels of endogenous Ac‐Tβ4 in serum, urine, or other organs of mice were not detected, but after administration of synthetic Ac‐Tβ4, they reported the detection of Ac‐Tβ4 in serum, urine, or other organs 30 .…”
Section: Discussionmentioning
confidence: 99%
“…The extent of acetylation of lysine residues may not be high compared with endogenous Ac‐Tβ4 in the intracellular environments. In case of trauma and wound conditions, intracellular Ac‐Tβ4 was released into the blood 29 . We assumed that the intracellular Ac‐Tβ4 form can be metabolized to the form with acetylated lysine residues that is distinguishable from the synthetic Ac‐Tβ4.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations